1135 Longer And More Frequent Naps Predict Incident Alzheimer's Dementia In Community-based Older Adults. (27th May 2020) - Li, P; Gao, L; Gaba, A; Yu, L; Buchman, A S; Bennett, D A; Hu, K; Leng, Y
Abstract: Introduction: Excessive napping duration has been associated with cognitive decline. The effect of napping frequency is less understood, and little is known about the development of Alzheimer's dementia associated with napping. We tested whether longer or more frequent naps in the elderly are linked to the development of incident Alzheimer's dementia. Methods: We studied 1, 180 older adults (age: 81.0±7.3 [SD]) in the Rush Memory and Aging Project who have been followed for up to 14 years. Motor activities of up to 10 days were recorded at baseline to assess napping characteristics objectively. We defined daytime napping episodes as motor activity segments between 10AM and 7PM with continuous zero-activity for ≥10min but <1h (to avoid off-wrist periods). Segments that were <5min apart were merged. Alzheimer's dementia diagnosis was determined using the criteria of the National Institute of Neurological and Communicative Disorders and Strone and the Alzheimer's Disease and Related Disorders Association. Cox proportional hazards models were performed to examine the associations of daily napping duration and frequency with incident AD. Results: Of 1, 180 non-demented participants at baseline (including 264 with mild cognitive impairment), 277 developed Alzheimer's dementia within 5.74±3.36 years. On average, participants napped for 38.3±1.0 (SE) min and1.56±0.04 (SE) times per day at baseline. After adjustment for age, sex, and education, every 30-min increase in daily napping duration was associated with a 20% increase in the risk of incident AD (95% confidence interval [CI]: 9%-31%; p=0.0002). One more nap per day was associated with a 19% increase in the risk of AD (95% CI: 8%-30%; p=0.0003). These associations remained after further adjustment for total sleep time. Conclusion: Longer and more frequent daytime naps predict a higher risk of incident Alzheimer's dementia. Future studies are needed to examine specific underlying mechanisms. Support: This work was supported by NIH grants RF1AG064312, RF1AG059867, R01AG017917, and R01AG56352.